Policies for the Development of Civil Servant Performance in the Regional Government of Bone Regency - M. Awaluddin; Andi Cahaya; Irmawati Irmawati; Anita Syam; Mashuri Mashuri; Maria Herlinda (Program Pascasarjana Universitas Negeri Makassar, 2021)
Globalization poses positive impacts such as advances in science and technology, facilitating the flow of information, communication, and distribution of goods and services. The negative impact of globalization is in the form of a threat to the nation's culture, the fading national identity, the dissolution of national borders, and the threat of other organizations. The impact of globalization is becoming an increasingly big and serious threat, especially when the organization lacks strong discipline. The purpose of this study is to find out how the performance of State Civil Apparatus, organizational culture concept framework, and efforts to improve the performance of Civil State Apparatus. The issue of Civil Servant performance will be accomplished and fulfilled if several factors influence it. One of the factors in question is organizational culture. Organizational culture is a philosophy, ideology, values, assumptions, beliefs, expectations, attitudes, and norms that are shared and binding in a particular community. Specifically in the culture within the organization will be determined by the conditions of the teamwork, leaders, and characteristics of the organization and the applicable administration process. Efforts to maintain the positive atmosphere of organizational culture will be able to improve employee performance, in other words, the better the organizational culture the higher the high level of performance, otherwise the worse the existing organizational culture the lower level of employee performance becomes low